2018
DOI: 10.1016/j.ejso.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Changes in volume, clinical practice and outcome after reorganisation of oesophago-gastric cancer care in England: A longitudinal observational study

Abstract: Centralisation of surgical services for O-G cancer in England has resulted in lower postoperative mortality. This cannot be explained by increased volume alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 15 publications
1
28
0
2
Order By: Relevance
“…Our study is limited by several factors including a lower number of resections and deaths compared with other published series, which has resulted in wide confidence intervals around the IRRs for some comparisons. As well, pathological stage and data on ASA scores were not available for approximately 20% of the study population.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Our study is limited by several factors including a lower number of resections and deaths compared with other published series, which has resulted in wide confidence intervals around the IRRs for some comparisons. As well, pathological stage and data on ASA scores were not available for approximately 20% of the study population.…”
Section: Discussionmentioning
confidence: 87%
“…Our findings are supported by reports of lower post-operative mortality following oesophagectomy and pancreaticoduodenectomy in high-volume compared with low-volume centres in several international population-level studies. 12,[15][16][17][18]30,31 As well, a recent large Australasian study of 2000 patients undergoing oesophagectomy reported significantly lower rates of in-hospital mortality following surgery in high compared with low-volume hospitals; 20 however, this study did not include mortality outcomes from 'for-profit' private hospitals which are estimated to account for nearly one-third of all oesophageal resections in Australia. 4 In these studies, 'high-volume' hospitals are defined as performing between 12 and 34 or more oesophagectomies 10,20,31 and between 20 and 97 or more pancreaticoduodenectomies 13,31,32 annually.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations